The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.2478/s11687-013-0107-5
|View full text |Cite
|
Sign up to set email alerts
|

Subulura mackoi n. sp. (Nematoda: Subuluridae) and the zoogeography of subulurids parasitizing birds

Abstract: A new nematode species, Subulura mackoi n. sp., is described based on specimens from the colon and caecum of the Eurasian Scops Owl Otus scops (L.) (Aves: Strigiformes) from the Czech Republic, collected in 2011. Males are characterized by 10 pairs of caudal papillae, a single papilla on the upper lip of the cloaca, and small unequal spiculae; female distinguishing features are body length, distance of the vulva from the anterior extremity, tail length, and egg dimension.Analysis of the zoogeographical distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In Subulura, the 11 other species have been reported from strigiform hosts, namely S. mackoi Baruš [1,4,12,[17][18][19]. With distinctly unequal spicules, S. mackoi, S. reclinata, S. acutissima, S. lutzi, S. longispicula and S. glaucidii can be easily distinguished from S. chinensis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Subulura, the 11 other species have been reported from strigiform hosts, namely S. mackoi Baruš [1,4,12,[17][18][19]. With distinctly unequal spicules, S. mackoi, S. reclinata, S. acutissima, S. lutzi, S. longispicula and S. glaucidii can be easily distinguished from S. chinensis.…”
Section: Discussionmentioning
confidence: 99%
“…Only S. lacertilia Vicente, Sluys, Fontes and Kiefer, 2000 is parasitic in lizards [6]. According to a previous study [4], over 60 valid species in Subulura have been reported worldwide. Among these, eight species have been recorded from China, namely S. halli Barreto, 1918, S. taiwanensis Yamaguti, 1936, S. citelli Sulimov, 1961, S. chinensis Schwartz, 1926, S. brumpti (Lopez-Neyra, 1922), S. suctoria (Molin, 1860), S. longispicula Wang, 1980 and S. tanjinensis Ming and Zhang, 2010 [3,5,[7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…This family is characterized by the structure of the buccal end in which the lobes of the oesophagus extend anteriorly to form a pharyngeal portion located between the true oral capsule and the oesophagus (Smales et al , 2021). Recent work has adopted scanning electron microscopy (SEM) as a complementary tool for the identification and redescription of species belonging to the superfamily Subuluroidea, contributing to a refined description of the species (Smales, 2009; Baruš et al , 2013; Du et al , 2014; Guo et al , 2019; Smales et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Species of the genus Subulura Molin, 1860 (Ascaridida: Subuluroidea) occur in birds, lizards and mammals, with more than 60 valid Subulura species reported worldwide (Vicente et al , 2000; Baruš et al , 2013). To date, four Subulura species have been reported parasitizing marsupials from South America: Subulura interrogans Lent & Freitas, 1935, S. Subulura Foster, 1939, Subulura trinitatis Wolfgang, 1951 and S. amazonica Pereira & Machado Filho, 1968, with only one Australian species, Subulura peramelis Baylis, 1930, reported.…”
Section: Introductionmentioning
confidence: 99%